European Economic and Monetary Union Sovereign Debt Markets - Sensoy, Ahmet; Hacihasanoglu, Erk; Rostom, Ahmed (World Bank Group, Washington, DC, 2015)
This paper focuses on developments in the European Economic and Monetary Union sovereign debt markets in the past decade. The first part analyzes the integration and segmentation structure of the bond markets of the Economic and Monetary Union before and after the sovereign debt crisis, by introducing the novel concept of correlation-based stable networks. Accordingly, a fair integration is observed between the bond markets during the pre-crisis period. However, a strict segmentation emerges, separating the members struggling with debt problems and the ones with relatively strong fiscal performances during the sovereign debt turmoil. The segmentation structure is clearly visualized, revealing the potential paths for crisis and recovery transmission in the future. In the second part, the paper comments on the recent decreasing trend in Economic and Monetary Union member bond yields and their increasing degree of co-movement. Accordingly, the paper argues that these changes do not depend on the fiscal performances of the member countries, but depend on the illusion of quality that appeared with the Fed (U.S. Federal Reserve) tapering signals in early 2013.